Black Arabs and African migrants: between slavery and racism in North Africa. Issue 1 (2nd January 2021) - King, Stephen J.
ABSTRACT: The popular uprisings for democracy, socio-economic justice, and dignity commonly referred to as the Arab Spring encompassed mobilisation against oppression by groups that have long experienced discrimination in the region. In North Africa, those groups included native Blacks that are mainly descendants of slaves (Black Arabs and Berbers) and tens of thousands of Black African migrants that have sought better life-opportunities in the Maghreb or clandestine passage to Europe via North Africa in the last two to three decades. This article traces the results of the largely novel mobilisation for equality by Blacks in North Africa during the Arab Spring. Progress towards racial equality has been uneven at best. In some areas, slavery and virulent racism have been reinvigorated. In others, Maghrebi white majorities have taken tentative steps to, for the first time, acknowledge their countries' legacies of racial slavery and oppression. This is most evident in the civil society associations, that include white members, which emerged to confront racism and slavery during the Arab Spring.